2020
DOI: 10.1038/s41467-020-18494-6
|View full text |Cite|
|
Sign up to set email alerts
|

Surfaceome dynamics reveal proteostasis-independent reorganization of neuronal surface proteins during development and synaptic plasticity

Abstract: Neurons are highly compartmentalized cells with tightly controlled subcellular protein organization. While brain transcriptome, connectome and global proteome maps are being generated, system-wide analysis of temporal protein dynamics at the subcellular level are currently lacking. Here, we perform a temporally-resolved surfaceome analysis of primary neuron cultures and reveal dynamic surface protein clusters that reflect the functional requirements during distinct stages of neuronal development. Direct compar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 93 publications
(141 reference statements)
1
33
0
Order By: Relevance
“…This limitation hinders us to properly track the translocation of EGFR from the cell membrane to the endosome. One possible way to solve this could be to apply surface protein labeling 58 before the subcellular protocol is performed, such that surface proteins could be separately purified from fraction 4.…”
Section: Discussionmentioning
confidence: 99%
“…This limitation hinders us to properly track the translocation of EGFR from the cell membrane to the endosome. One possible way to solve this could be to apply surface protein labeling 58 before the subcellular protocol is performed, such that surface proteins could be separately purified from fraction 4.…”
Section: Discussionmentioning
confidence: 99%
“…This limitation impedes us to properly track the translocation of EGFR from the cell membrane to the endosome. One possible way to solve this could be to apply surface protein labeling 47 before the subcellular protocol is performed, such that surface proteins could be separately purified from fraction 4.…”
Section: Discussionmentioning
confidence: 99%
“…Classification of cellular identities using the homeo-code allowed us to systematically investigate the CSP distribution between cells. Interestingly, most CSPs change more gradually between cells, and unlike homeodomain TF expression, the binary expression of Ig proteins alone is insufficient to specify single cells (De Wit & Ghosh, 2016;van Oostrum et al, 2020). Previous studies on single molecules even indicated that already small changes in relative expression levels of CSPs in matching partners can change synaptic specificity (Sweeney et al, 2012;Yogev & Shen, 2014).…”
Section: Discussionmentioning
confidence: 99%